IMPLEMENTATION OF ENVIRONMENTAL ACCOUNTING AS SOCIAL RESPONSIBILITY AT ASY SYIFA HUSADA TAKERAN CLINIC - Saputri, Fathin Ekowati; Elva Nuraina; Elly Astuti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to determine accounting treatment, including environmental budgets inenvironmental preservation and the implementation of environmental accounting associal responsibility at the Asy-Syifa Husada Clinic. In this study, we are applyingdescriptive qualitative research methods. Primary data sources. Data collectiontechniques in this study include interviews, documentation, and observation. This studyuses data analysis, namely, data reduction, verification, and display data. The resultsin this study that the Asy-Syifa Takeran Magetan clinic has implementedenvironmental accounting seen from the cost structure of the proposed environmentalcosts included in the operational cost component in the income statement. However,there are several elements of environmental costs that are not classified accordingly.